The Influence of Student Perceptions about Google Classroom on Interest in Religious Learning at SMPN 1 Ngoro Jombang - Alfiyah, Nur; Asrori, Mohammad; Khudriyah, Khudriyah (The Magister of Islamic Education IAIN Pontianak, 2025)
Google classroom is a web and mobile-based application which is able to be used as an online learning media. Google classroom as an internet-based service with e-learning system assumed to facilitate the learning. This study aims to know whether or not google classroom affect students' learning interests of religious subjects at SMP Negeri 1 Ngoro Jombang. This research design is quantitative, with exposed-facto approach. The population of this study was VII grade student of SMP Negeri 1 Ngoro Jombang. The sample was 72 students (25% from population) which were selected through simple random sampling. The research instrument was questionnaire, the data then analyzed by simple linear regression. The results showed that students' perception of google classroom was in the medium category (61% of respondents had score between 32 to 38). The student’s interest of religious learning was also in the medium category, which is 64% or 46 respondents had score between 33 to 41. The hypothesis result showed that there is low influence (8%) between students' perception of google classroom towards the religious learning interest in SMP Negeri 1 Ngoro Jombang.